2023
DOI: 10.2147/jir.s439604
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Insights into the Pathogenesis of Ankylosing Spondylitis

Zhenhua Liu,
Mingxi Cai,
Haoteng Ke
et al.

Abstract: Purpose of the Review: Emerging evidence has shown that ankylosing spondylitis fibroblasts (ASFs) act as crucial participants in inflammation and abnormal ossification in ankylosing spondylitis (AS). This review examines the investigations into ASFs and their pathological behavior, which contributes to inflammatory microenvironments and abnormal bone formation. The review spans the period from 2000 to 2023, with a primary focus on the most recent decade. Additionally, the review provides an in-depth discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Pirfenidone possesses anti-inflammatory and antifibrotic properties; its mechanisms include inhibition of TGF-β-induced fibroblast proliferation and suppression of inflammatory mediator production ( 58 ). Given the chronic inflammation and potential fibrosis in the pathological process of AS, including new bone formation ( 59 ), pirfenidone may have potential therapeutic utility in the treatment of AS. Due to the critical role of MAPK14 in regulating inflammation, inhibitors targeting this protein may lead to adverse effects, such as immunosuppression ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pirfenidone possesses anti-inflammatory and antifibrotic properties; its mechanisms include inhibition of TGF-β-induced fibroblast proliferation and suppression of inflammatory mediator production ( 58 ). Given the chronic inflammation and potential fibrosis in the pathological process of AS, including new bone formation ( 59 ), pirfenidone may have potential therapeutic utility in the treatment of AS. Due to the critical role of MAPK14 in regulating inflammation, inhibitors targeting this protein may lead to adverse effects, such as immunosuppression ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mesenchymal stem cells (MSCs), was reported that may resulting in AS in the conditions of oxidative stress-mediated mitochondrial dysfunction ( Ye et al, 2020 ) and TNF-α-mediated m6A modification of ELMO1 ( Xie et al, 2021 ). Likewise, ankylosing spondylitis fibroblasts (ASFs) can also influence the progression of AS by promoting joint remodeling, affecting fat enrichment and activating as myofibroblasts to form extracellular matrix independent of inflammation ( Liu et al, 2023 ). Given that dysregulation of inflammatory responses are primary manifestations of AS, treatment strategies primarily focus on non-steroidal anti-inflammatory drugs and biologics, including tumor necrosis factor inhibitors and interleukin-17 inhibitors ( Deodhar et al, 2020 ; Tam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%